2020
DOI: 10.3390/microorganisms8091341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biodegradation Efficiency of Four Various Types of Plastics by Pseudomonas aeruginosa Isolated from the Gut Extract of Superworms

Abstract: Plastic waste worldwide is becoming a serious pollution problem for the planet. Various physical and chemical methods have been tested in attempts to remove plastic dumps. However, these have usually resulted in secondary pollution issues. Recently, the biodegradation of plastic by fungal and bacterial strains has been spotlighted as a promising solution to remove plastic wastes without generating secondary pollution. We have previously reported that a Pseudomonas aeruginosa strain isolated from the gut of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 43 publications
(67 reference statements)
2
26
0
Order By: Relevance
“…Surface alterations of the plastics are characteristic of the aging processes occurring under the influence of microorganisms (present in the intestines of insects) or, more specifically, enzymes secreted by them. The folding of the previously smooth surface of the polymer and the formation of pitting was observed during the biodegradation of PS and PE with the bacterium P. aeruginosa isolated from the gut of Zophobas morio insect (Tenebrionidae; cousin of mealworm, known also as superworm) [52]. Surface elements mapping comparison of PS and PE before and after biodegradation showed that those changes were connected with increase in oxygen content, which suggests oxidative changes in the plastics [52].…”
Section: Polymers Surface Alterations Visualized By Semmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface alterations of the plastics are characteristic of the aging processes occurring under the influence of microorganisms (present in the intestines of insects) or, more specifically, enzymes secreted by them. The folding of the previously smooth surface of the polymer and the formation of pitting was observed during the biodegradation of PS and PE with the bacterium P. aeruginosa isolated from the gut of Zophobas morio insect (Tenebrionidae; cousin of mealworm, known also as superworm) [52]. Surface elements mapping comparison of PS and PE before and after biodegradation showed that those changes were connected with increase in oxygen content, which suggests oxidative changes in the plastics [52].…”
Section: Polymers Surface Alterations Visualized By Semmentioning
confidence: 99%
“…The folding of the previously smooth surface of the polymer and the formation of pitting was observed during the biodegradation of PS and PE with the bacterium P. aeruginosa isolated from the gut of Zophobas morio insect (Tenebrionidae; cousin of mealworm, known also as superworm) [52]. Surface elements mapping comparison of PS and PE before and after biodegradation showed that those changes were connected with increase in oxygen content, which suggests oxidative changes in the plastics [52]. Similar changes as observed by us in the case of PU foams had been observed by [53] after biodegradation trials in soil burial.…”
Section: Polymers Surface Alterations Visualized By Semmentioning
confidence: 99%
“…On the other hand, a mealworm managed to mineralize 49% of LDPE foam after a month ( Brandon et al, 2018 ). Gut microbiome seems to change with PE-diet and some of the abundant strains have been isolated and tested against the polymer by themselves, however biodegradation proceeds in a much slower rate and extent ( Yang et al, 2014 ; Brandon et al, 2018 ; Lee et al, 2020 ).…”
Section: Microbial and Enzymatic Degradation Of Plasticsmentioning
confidence: 99%
“…Interstingly, their value comes in dealing with plastic waste, particularly polystyrene (PS) and polyethylene(PE). It is their ability of consuming and mineralizing PS & PE [16,35] that would be the focus of their contribution to the circular economy of plastic waste.…”
Section: Zophobas Morio and Tenebrio Molitor In The Circular Economymentioning
confidence: 99%